GST genes polymorphisms and the risk of colorectal cancer development - Klusek, Justyna; Głuszek, Stanisław; Klusek, Jolanta (Contemporary Oncology/Współczesna Onkologia, 2014)
Increasingly often, molecular studies of colorectal cancer focus on low penetrance genes. Among the factors potentially modifying the risk of contracting colorectal cancer is the glutathione S-transferase (GST) gene family, encoding enzymes of the glutathione transferase type. Proteins of the GST family (glutathione S-transferases) are enzymes detoxifying a wide range of hazardous substances, such as reactive oxygen species (ROS) or xenobionts. Thus, their role, among other things, is the protection of DNA against oxidative damage, which may lead to mutations, and in consequence, favour carcinogenesis. GST gene polymorphisms may affect the functioning of the encoded enzymes, exerting an effect on the level of DNA damage, and therefore may have an indirect influence on the risk of the development of cancer. At present, there are many studies available concerning GST gene polymorphisms as factors modulating the risk of developing cancer, including colorectal cancer.